The clean development mechanism potential of a combined heat and power plant in Stellenbosch, South Africa - Bellingham, Christopher Grant (Department of Mechanical Engineering, 2014)
Only 50-60% of the roundwood volume harvested by commercial sawmills in South Africa is sold as timber. The rest is sold as timber by-products, utilised as fuel in sawmill boilers, or disposed of as waste res idues. This dissertation assesses the Clean Development Mechanism (CDM) potential of a proposed Combined Heat and Power (CHP) plant that will utilise a sawmill's byproducts, or waste residues, as its fuel source; the sawmill is located in Stellenbosch, South Africa. The sawmill employs standard production techniques as found in large sawmills throughout South Africa, enabling the results of this dissertation to be utilised as a reference for South Africa's total sawmill CHP potential. The CHP plant's emission neutral energy will replace fossil-fuelled energy, thus offsetting Greenhouse Gas (GHG) emissions. The plant will generate revenue from the sale of GHG emission credits, in addition to electricity and other products. The proposed CHP plant has the potential to reduce annually more GHG than any other CDM project currently registered in South Africa. In addition to the environmental benefit, the plant will require labour for its construction and operation, resulting in job creation and skills development.